A mitochondria-to-nucleus regulation mediated by the nuclear-translocated mitochondrial lncRNAs. - Jia Li; Ruoling Bai; Yulian Zhou; Xu Song; Ling Li (PLoS Genetics)
A bidirectional nucleus-mitochondria communication is essential for homeostasis and stress. By acting as critical molecules, the nuclear-encoded lncRNAs (nulncRNAs) have been implicated in the nucleus-to-mitochondria anterograde regulation. However, role of mitochondrial-derived lncRNAs (mtlncRNAs) in the mitochondria-to-nucleus retrograde regulation remains elusive. Here, we identify functional implication of the mtlncRNAs MDL1AS, lncND5 and lncCyt b in retrograde regulation. Mediated by HuR and PNPT1 proteins, the mtlncRNAs undergo a mitochondria-to-nucleus traveling and then regulate a network of nuclear genes. Moreover, as an example of the functional consequence, we showed that the nuclear-translocated lncCyt b cooperates with the splicing factor hnRNPA2B1 to influence several aspects of cell metabolism including glycolysis, possibly through their regulatory effect on the post-transcriptional processing of related nuclear genes. This study advances our knowledge in mitochondrial biology and provides new insights into the role of mtlncRNAs in mitochondria-nucleus communications.